Reluctant warriors : Germany, Japan, and their U.S. alliance dilemma - Sakaki, Alexandra; Maull, Hanns, 1947-; Lukner, Kerstin; Krauss, Ellis S.; Berger, Thomas U. (Brookings Institution Press, 2020)
"Since the end of World War II, Germany and Japan have been the most reluctant of all major U.S. allies to take on military responsibilities. Given their histories, this reluctance certainly is understandable. But because of their size and economic importance, Germany and Japan are the most important U.S. allies in Europe and in East Asia, respectively, and their long-term reluctance to share the defense burden has become a perennial source of frustration for Washington. The potential security roles of Germany and Japan are becoming increasingly important given the uncertainty, indeed volatility, of today's international environment. Under President Trump, friction among allies over burden-sharing is more intense than ever before. Meanwhile, the security environments in Europe and Asia have deteriorated because of the resurgence of a belligerent Russia under Vladimir Putin, the steady rise of an increasingly assertive China, and North Korea's worrisome acquisition of nuclear weapons. Partly in response to these developments, Germany and Japan in recent years have boosted their security efforts, mainly by increasing defense spending and taking on a somewhat broader range of military missions. Even so, because of their cultures of anti-militarism resistance remains strong in both countries to rebuilding the military and assuming more responsibility for sustaining regional or even global peace. In Reluctant Warriors, a team of noted international experts critically examines how and why Germany and Japan have modified their military postures since 1990 so far, and assesses how far the countries still have to go -- and why. The contributors also highlight the risks the United States takes if it makes too simplistic a demand for the two countries to 'do more.'"--